2007
DOI: 10.1021/ct7000254
|View full text |Cite
|
Sign up to set email alerts
|

Homoleptic Carbonyls of the Second-Row Transition Metals:  Evaluation of Hartree−Fock and Density Functional Theory Methods

Abstract: The homoleptic mono- and multinuclear carbonyls for Mo, Tc, Ru, and Rh, namely, Mo(CO)6, Ru(CO)5, Tc2(CO)10, Ru3(CO)12, Rh4(CO)12, and Rh6(CO)16, are investigated theoretically by the Hartree-Fock method and three density functional theory (DFT) methods, i.e., BP86, B3LYP, and MPW1PW91, along with the SDD ECP basis sets. The results predicted by all the methods are basically in agreement with each other. The MPW1PW91 and BP86 methods predict geometric parameters and vibrational spectra, respectively, closest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 79 publications
3
62
0
1
Order By: Relevance
“…[24] The MPW1PW91 functional has been shown to be typically more reliable than the first generation functionals for carbonyl derivatives of the second and third row transition metals. [25,26] For the third-row transition-metal derivatives effective core potential (ECP) and related basis sets provide a simple but efficient approach for reducing the computational effort while considering relativistic effects. In this study the ECP basis set SDD (Stuttgart-Dresden ECP plus DZ), [27,28] is used for the tungsten atom.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] The MPW1PW91 functional has been shown to be typically more reliable than the first generation functionals for carbonyl derivatives of the second and third row transition metals. [25,26] For the third-row transition-metal derivatives effective core potential (ECP) and related basis sets provide a simple but efficient approach for reducing the computational effort while considering relativistic effects. In this study the ECP basis set SDD (Stuttgart-Dresden ECP plus DZ), [27,28] is used for the tungsten atom.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[32] In the present study, the MPW1PW91 and BP86 methods are found to agree fairly well with each other in predicting the structures of the (R 2 C 2 ) 3 W(CO) n (R = CH 3 , CF 3 ) derivatives. Since previous work [25] indicates that the MPW1PW91 method generally gives closer agreement with experimental bond lengths, the bond lengths obtained by the MPW1PW91 method are given in the discussion unless otherwise indicated. A total of 24 structures for the neutral (R 2 C 2 ) 3 W(CO) n (R = CH 3 ,CF 3 ) (n = 3, 2, 1, 0) compounds are reported in this paper.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30] Extensive experience suggests that the pure GGA functional BP86 is often more reliable for many organometallic systems than the popular hybrid functional B3LYP when compared with available experimental results. [17,31,32,33] In the present study, complete geometrical optimization and vibrational frequency analyses were carried out using the DFT functional BP86 with DZP basis sets. The BP86 functional combines Becke's 1988 exchange functional (B) with Perdew's 1986 correlation functional.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…The isoelectronic species Cp 2 Co 2 (CO) was reinvestigated [32] for comparison with Cp 2 FeNi(CO) using the same level of theory. The singlet states of Cp 2 Co 2 (CO) were studied in the previous work using a coarser integration grid (75,302) than the (99,590) integration grid used in this work; this leads to some significant imaginary frequencies.…”
Section: Cp 2 Feni(co) Vs Cp 2 Co 2 (Co)mentioning
confidence: 99%
“…But unlike the vast variety of NMR parameters of 20 mono-and bi-nuclear [8][9][10][11][12][13][14] carbonyls studied by our group of workers 1,4 ,only a little had been reported on NMR studies by computational methods for poly-nuclear [18][19][20][21][22] carbonyls as follows:…”
Section: Introductionmentioning
confidence: 99%